Quota Formula Review : Data Update and Further Considerations. (Policy Papers; Policy Paper, 2012)
This Annex presents additional staff work on financial interconnectedness. The analysis examines a possible methodology for constructing indicators of financial interconnectedness and related data issues. In addition, it presents some illustrative simulation results.This annex focuses on financial interconnectedness that takes into account the pattern and size of cross-border financial linkages and potentially provides a more comprehensive picture of a country's international financial integration.